Atividade antioxidante do extrato seco de cacau orgânico (Theobroma cacao): estudo de estabilidade e teste de aceitação de cremes acrescidos deste extrato - Silva, Silas Arandas Monteiro e; Valarini, Michele Fernanda Costa; Chorilli, Marlus [UNESP]; Venturini, Anna; Leonardi, Gislaine Ricci (My University, 2013)
The cocoa fruit (Theobroma cacao) is known worldwide for its richness in fatty acids and phenolic compounds, with antioxidant power, and it is known to be composed of more than 50% medium-chain fatty acids, making it a raw material that could be exploited by the food, pharmaceutical and cosmetics industries. The aim of this study was to assess the antioxidant power of organic cocoa dried extract, to develop cosmetic formulations from this extract and to determine their stability and carry out rheological tests, liquid-crystal research and acceptance testing on them. The plant extract was assayed for its antioxidant power by the DPPH radical scavenging method. Cosmetic formulations were produced and samples were subjected to physicochemical stability tests (organoleptic assessment, centrifugal testing and determination of pH), rheological characterization and polarized light microscopy analysis. The stable preparations were also evaluated for their acceptability by consumers. From the results presented, it was possible to characterize the antioxidant activity of dried organic cocoa extract and to prepare cosmetic preparations containing 5% of this active compound. These showed pseudoplastic behavior associated with thixotropy and lamellar liquid crystals were present at all storage times and temperatures. It was also found that the higher self-emulsifying wax contents interfered with consumer acceptance of the cosmetic product.

Os frutos de cacau (Theobroma cacao) são conhecidos mundialmente pela sua riqueza em ácidos graxos e compostos fenólicos com poder antioxidante, sendo que em sua constituição é possível relatar mais de 50% em ácidos graxos de cadeia média que o torna matéria-prima passível de ser explorada pela indústria alimentícia, farmacêutica e cosmética. Este trabalho teve como objetivo estudar o poder antioxidante do extrato seco de cacau orgânico, obter formulações cosméticas acrescidas deste extrato, promovendo os estudos de estabilidade, ensaios reológicos e a investigação de cristais-líquidos, bem como realizar o teste de aceitação das mesmas. O extrato vegetal foi avaliado quanto seu poder antioxidante pelo método de sequestro radicalar DPPH. Formulações cosméticas foram obtidas e amostras foram submetidas a ensaios físico-químicos de estabilidade (caracterização organoléptica, teste de centrífuga e determinação dos valores de pH), caracterização reológica, assim como análises em microscopia de luz polarizada. As preparações estáveis também foram avaliadas quanto a sua aceitabilidade por provadores. A partir dos resultados apresentados pôde-se constatar a atividade antioxidante do extrato seco de cacau orgânico e obter preparações cosméticas, constituídas deste ativo a 5%, com comportamento pseudoplástico associado à tixotropia e providas de cristais líquidos lamelares. Verificou-se também que a concentração de cera autoemulsionante interferiu na aceitação do produto cosmético.
Antioxidant activity of organic cocoa dried extract (Theobroma cacao), stability study and acceptance testing of cosmetic cream containing this extract
Keywords: Cosmetics; Acceptance test; Liquid crystals; Cocoa; Rheology; Cosméticos; Teste de aceitação; Cristais líquidos; Cacau; Reologia